1998
DOI: 10.2135/cropsci1998.0011183x003800050011x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Alfalfa to Stem‐Tip Inoculations with Five Isolates of Sclerotinia trifoliorum

Abstract: Effective breeding for economically important resistance to Sclerotinia trifoliorum Eriks in alfalfa (Medicago saliva L.) requires that the plant breeder have an understanding of any genetic basis for variability in measurements of resistance and the likelihood that selection for resistance to one isolate confers resistance to other isolates. Fifty alfalfa plants were repeatedly evaluated for their resistance to five isolates of S. trifoliorum. Tips of excised stems were inoculated with a S. trifoliorum isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Accordingly, Vå 092001 originating from a region in Norway where clover rot does not occur, was the most susceptible cv. This is in general agreement with Halimi et al. (1998), who found that alfalfa selected for resistance to one isolate of S. trifoliorum was also resistant to others.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Accordingly, Vå 092001 originating from a region in Norway where clover rot does not occur, was the most susceptible cv. This is in general agreement with Halimi et al. (1998), who found that alfalfa selected for resistance to one isolate of S. trifoliorum was also resistant to others.…”
Section: Discussionsupporting
confidence: 92%
“…This is not surprising, considering this fungus’ mode of sexual reproduction. Halimi et al. (1998) stated that aggressiveness differs among isolates of S. trifoliorum , but that no pathological races exist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, resistance breeding is efficient only when based on the recurrent selection strategy which in turn requires even more resources [6]. There are several methods developed which enable to screen breeding material in laboratory and greenhouse conditions [7,8]. However, they are more suitable for the search of resistant material for creating new cross combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Also in alfalfa, divergent selection for resistance to sclerotinia crown and stem rot (Sclerotinia trifoliorum Eriks.) using excised stems revealed significant differences in disease reactions between the selected populations (Halimi et al 1998). In addition, certain physical properties such as stem cell wall content and cuticle thickness may contribute to post-harvest resistance in alfalfa, as suggested by Babij (1997).…”
mentioning
confidence: 99%